2017
DOI: 10.1016/j.annemergmed.2017.03.058
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Emergency Medical Services Use by Older Adults: Analysis of a Comprehensive Statewide Database

Abstract: OBJECTIVE The objective of this study was to characterize repeat Emergency Medical Services (EMS) transports among older adults across a large and socioeconomically diverse region. METHODS Using the North Carolina Prehospital Medical Information System (PreMIS), we analyzed the frequency of repeat EMS transports within 30 days of an index EMS transport among adults aged 65 years and older from 2010–2015. We used multivariable logistic regressions to determine characteristics associated with repeat EMS transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 39 publications
(40 reference statements)
3
34
0
1
Order By: Relevance
“…But the figure is also higher than international studies involving solely patients ≥65 years old showing that 44% to 88% of patients were conveyed. [8][9][10] Differences in ambulance service organisations between and within countries, however, make international comparison difficult based on varying, for example, care level options, 21 and continuity of care. 22 Previous studies have found that 7%-16% of patients engaging AAs have symptoms that can be treated at the primary care level, 23 24 indicating that more patients can receive optimal out-of-hospital care through extended Open access collaboration between organisations within the emergency care system.…”
Section: Results Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the figure is also higher than international studies involving solely patients ≥65 years old showing that 44% to 88% of patients were conveyed. [8][9][10] Differences in ambulance service organisations between and within countries, however, make international comparison difficult based on varying, for example, care level options, 21 and continuity of care. 22 Previous studies have found that 7%-16% of patients engaging AAs have symptoms that can be treated at the primary care level, 23 24 indicating that more patients can receive optimal out-of-hospital care through extended Open access collaboration between organisations within the emergency care system.…”
Section: Results Discussionmentioning
confidence: 99%
“…7 Internationally, patients ≥65 years old represent 30%-50% of all ambulance assignments (AAs), and 44%-88% are conveyed to hospitals. [8][9][10] During each AA, the ambulance personnel provide assessment and decide on optimal care level for patients' disposition, 11 meaning where patients are treated or conveyed for optimal care. Patients' dispositions during AAs are in this study divided into conveyance or non-conveyance to hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the World Health Organization strongly recommends that health care systems globally redesign their services to better fulfill older people's needs and to promote their independence [1]. Older age entails prevalence of cognitive and physical impairments, chronic medical conditions, and frailty, thus increasing the need for emergency ambulance care [2][3][4][5][6]. Currently, approximately 1.5 million people in Sweden are aged > 70 years [7], a population that is estimated to rise by 25% over the next 15 years [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, older adults have a high rate of emergency department (ED) attendance, with one of every five visiting the ED at least once a year . Older adults account for up to 25% of all emergency department (ED) patient encounters and for 38% of emergency medical services (EMS) transports . This number will rise dramatically: in 2018, roughly one in seven Americans was an older adult; by 2030, that figure will be one in five.…”
mentioning
confidence: 99%